Do public wages in the euro area explain private wage developments? An empirical investigation - Attinasi, Maria-Grazia; Berardini, Francesco; Palazzo, Alessandra Anna (Frankfurt am Main, 2019)
"This paper investigates the relationship between public and private wages in the five largest euro area countries for the period 1997-2017. The analysis shows that there exists a positive and significant response of private wages to a public wage shock. This effect is found to be temporary and to differ across countries (positive and significant in France, Spain, Italy and non-significant in Germany and the Netherlands). Interestingly, the response of private wages is found to be asymmetric: a positive and statistically significant response is found in case of a positive shock to public wages, while no statistically significant effects are detected in case of a cut to public wages. As the public wage containment policies adopted during the sovereign debt crisis are expected to be gradually lifted in several euro area countries, the findings of this paper suggest that knock-on effects on private sector wages cannot be excluded in the years to come."